Concentração sérica de homocisteína em cães doentes renais crônicos - Guilherme Henrique Costa Silva (2023)
With the increase in the longevity of companion animals and the existence of certain endemic diseases that compromise the renal function of dogs and cats, chronic kidney disease has become an increasingly prevalent condition in the clinical routine. Early diagnosis is essential for the adoption of appropriate therapeutic measures before significant loss of renal functional mass. The currently most used method often has low correlation with the glomerular filtration rate at low levels of renal dysfunction, which delays the diagnosis and the success of interventional measures. In medicine, circulating levels of homocysteine have been shown to be inversely proportional to declining renal function, although in veterinary medicine, the number of works with this analyte is still small. This work aims to verify, through a clinical trial with animals with chronic kidney disease, the relationships between plasma concentrations of homocysteine and kidney function. 5 healthy dogs and 16 with CKD were admitted to the study and submitted to clinical and laboratory evaluation, with patients with CKD evaluated at 4 different times, under the effect of conservative treatment. The concentration of homocysteine was evaluated in plasma samples over these 4 times, showing that it was higher in patients with CKD compared to healthy patients and that the higher the stage of the disease, the higher the levels of hyperhomocysteinemia . This finding highlights the potential use of this molecule as a biomarker of renal disfunction.